High-dietary fibers cereal bars containing malt bagasse by-product from the brewing industry - Caroline Tombini
The aim of this study was to use the malt bagasse by-product for developing high-dietary fibers cereal bars. Three formulations were tested and contained 0% (control), 19% and 24% of malt bagasse. The bars with malt bagasse were rich in dietary fiber and protein, with 6.06 and 26.35 g/100 g, respectively for samples with 19% of bagasse, and 8.43 and 26.22 g/100 g, respectively, for bars with 24% of this by-product. The total phenol content (TPC) of the bars with 19 and 24% of bagasse, was 100.37 and 192.13 mg GAE/100 g of sample, and the EC50 was 21.58 and 14.78 mg/mL (DPPH assay), respectively. The incorporation of this by-product into the formulations enhanced their TPC and antioxidant capacity. These samples had a high sensory acceptance. The formulation with the lowest malt bagasse concentration showed high global acceptance (56%) and purchase intention. The sensory attributes that pleased the tasters the most, rated as "liked moderately," were the color and odor of both bars. Cereal bars showed an improved nutritional composition and antioxidant capacity after malt bagasse addition, and the formulation with 19% should be the best choice among the tested formulations, when considering the set of nutritional and sensory aspects. The malt bagasse was successfully valorized as an ingredient in a functional food, whilst contributing to the environment.